A supramolecular cavitand for selective chromatographic separation of peptides using LC-MS/MS: a combined in silico and experimental approach. (9th December 2020) - Mekapothula, Subbareddy; Wonanke, A. D. Dinga; Addicoat, Matthew A.; Wallis, John D.; Boocock, David J.; Cave, Gareth W. V.
Abstract : The chromatographic separation of proteomic standards via a silica immobilized pillararene cavitand has been designed in silico using host–guest binding energy studies and realized experimentally to selectively interact with peptides. Abstract : The effective separation of a mixed peptide sample has been achieved via a computational strategy towards the bespoke design of a new silica bound supramolecular host capable of selectively interacting with different peptides via their morphology and amino acid functionalities. The experimental and in silico chromatographic behaviour of a sample of mixed peptides on a new co-pillar[4+1]arene bound silica HPLC stationary phase column was compared with RP-C18 and unfunctionalized silica (normal phase) column via liquid chromatography coupled with mass spectrometry (LC-MS/MS) and demonstrates superior separation selectivity and sensitivity for the mixed peptide solution being investigated.